Analisis Permasalahan dan Pendapatan Usaha Budidaya Ikan Nila di Kecamatan Loa Kulu Kabupaten Kutai Kartanegara - Baiq Sulistyo Rini; Helminuddin Helminuddin; Fitriyana Fitriyana; Elly Purnamasari; Etik Sulistyowati Ningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
The aimed of this research was to analyzing the problems and income of fish farming businesses in Loa Kulu District, Kutai Kartanegara Regency. This study used qualitative descriptive analysis methods and income analysis. The results of the study showed that the problems faced by fish farmers in Loa Kulu District, Kutai Kartanegara Regency related to fish farming (tilapia fish breeding and enlargement) were the problem of uncertain water quality in the Mahakam River, flooding in fish seed cultivation ponds, and lack of information on disease control in cultivation activities and complaints about slow fish growth in several cultivation locations. The amount of income from 19 fish farmers who carried out seed farming businesses was in the interval of IDR 48,131,090.48 / year to IDR 767,232,756.71 / year with an average of IDR 260,778,413.40 / year per respondent or IDR 21,731,534.45 / month per respondent. The amount of income from 23 fish farmers who run fish farming businesses is in the interval of IDR 81,245,257.14/year to IDR 2,908,679,785.71/year with an average of IDR 1,153,670,371.64/year per respondent or IDR 96,139,197.64/month per respondent.